Sistemas de transformação e suas relações com a erosão hídrica em solos de textura média em Terra Roxa-PR - Sanches, Rafael Martins (2017)
The study of the structure and functioning of the landscape implies the understanding of natural and anthropic processes that involve a certain segment of space. Therefore, studies are necessary to understand the distribution of soils in the landscape and their relationship with relief forms. In this sense, it was sought to map, vertically and laterally, the pedological cover along a morphologically representative slope of the municipality of Terra Roxa. It is a contextualized area in the landscape unit of Guaíra and is inserted in the Paraná III Hydrographic Basin, in the western region of Paraná. The methodology of the Structural Analysis of Pedestrian Coverage guided the research stages, proceeding with topographic survey, pedological recognition, opening of trenches for the macromorphological description of the horizons and collection of deformed and undisturbed samples for physical and chemical analysis. These procedures allowed the confirmation of a pedological system with the presence of top and high-slope Oxisols (LVd), Ultisols (PVd) in all medium-strand and Ultisols, downstream from the slope break. The occurrence of these classes of soils occurs due to a relief with a low degree of dissection and a maximum slope of 8%, a smoothly undulating plane, characterized by wide choline and flattened top, with convergent-convex-concave slope and open V-valley . As a result of the pedological cover resulting from sedimentary rocks of the Caiuá Formation, the soils present a sandy-medium texture with high sand content (> 60%) and low clay content (<25%), of a friable and susceptible to occurrence of water erosion in the downstream segment. In this sector of the slope predominate soils with horizon E, sandy (up to 88%) and subsurface horizon of impediment (Btg and Bt). This pedomorphological organization points to the existence of two transformation fronts: one in the middle-slope (Bw / Bt transition) and the other in the low-slope (transition AB / E and E / Bt), where the erosive instability of the pedological system.